PURWAKARTA LAYAK ANAK - Nur Aisah Jamil; Ike Nilawati Rohaenah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Purwakarta child-friendly is the availability of cities for children. Availability of children's needs such as; 1) Providing access to health services, education, clean water, sanitation that is healthy and free from environmental pollution. 2) Provide policies and budgets specifically for children. 3). Provide a safe and comfortable environment, allowing children to develop. Children can enjoy, learn, interact socially, develop psychosocial and cultural expressions. 4). Balance in the social, economic field, and protected from the effects of environmental damage and natural disasters. 5). Give special attention to children such as living and working in the streets, sexual exploitation, living with disabilities or without parental support and, 6. There is a place for children to participate in making decisions that directly affect their lives. Child-friendly city is very important to be fulfilled. And included in the APBD budget. The Purwakarta program is suitable for children to be supported by the government. Private and public.